Identifying drug substances of screening tool for older persons’ appropriate prescriptions for Japanese - Kaori Nomura (BMC Geriatrics, 2018)
Abstract Background In 2015, the Japan Geriatric Society (JGS) updated “the Guidelines for Medical Treatment and its Safety in the elderly,” accompanied with the Screening Tool for Older Persons’ Appropriate Prescriptions for Japanese (STOPP-J): “drugs to be prescribed with special caution” and “drugs to consider starting.” The JGS proposed the STOPP-J to contribute to improving prescribing quality; however, each decision should be carefully based on medical knowledge. The STOPP-J shows examples of commonly prescribed drug substances, but not all relevant drugs. This research aimed to identify substances using such coding, as a standardized classification system would support medication monitoring and pharmacoepidemiologic research using such health-related information. Methods A voluntary team of three physicians and two pharmacists identified possible approved medicines based on the STOPP-J, and matched certain drug substances to the Anatomical Therapeutic Chemical Classification (ATC) and the Japanese price list as of 2017 February. Injectables and externally used drugs were excluded, except for self-injecting insulin, since the STOPP-J guidelines are intended to cover medicines used chronically for more than one month. Some vaccines are not available in the Japanese price list since they not reimbursed through the national health insurance. Results The ATC 5th level was not available for 39 of the 235 identified substances, resulting in their classification at the ATC 4th level. Furthermore, among 26 combinations, 10 products were matched directly to the ATC 5th level of the exact substances, and others were linked to the ATC representing the combination or divided into multiple substances for classification if the combination was not listed in the ATC. Conclusion This initial work demonstrates the challenge of matching ATC codes and the Japan standard commodity classification codes corresponding to STOPP-J substances. Since coding facilitates database analysis, the proposed drug list could be applied to research using large databases to examine prescribing patterns in patients older than 75 years or who are frail. Since ATC is not available for some substances, Japanese medicines need the process to be registered in the ATC for an effective screening tool to be developed for STOPP-J.